POLITICAL AND CULTURAL COOPERATION BETWEEN UZBEKISTAN AND TURKEY THE BEGINNING OF A NEW ERA - Khurshid Dilliyev (Web of Journals Publishing, 2024)
This article focuses on issues related to the integration of Uzbekistan into the world community, taking a proper place in the system of international relations, and the political and cultural cooperation of Uzbekistan with Turkey. In the article, information related to the new era of political and cultural relations between Uzbekistan and Turkey was studied on a scientific and creative basis and analytical conclusions were drawn. In addition, problematic situations that arose in the establishment of political and cultural relations between Uzbekistan and Turkey were also studied. Taking this into account, this article serves as an important resource for researchers in the field of political and cultural relations between Uzbekistan and Turkey.
Keywords: President, political, political cooperation, cultural relations, strategic partnership, Oliy Majlis, Grand National Assembly, government, parliament, public, circle of businessmen, cultural event.